The need for best practices in digital content syn - Franganillo, Jorge (Anuario ThinkEPI, 2008)
Distributing news summaries by means of content syndication significantly improved access to current information, but has had only moderate acceptance despite optimistic predictions. Inadequate attention to best practice by many content producers have limited the usefulness of content syndication. In order for this redistribution method to become a truly beneficial tool, producers must provide good content, create value, and achieve greater empathy with users.
Keywords: Content syndication; RSS; Good practices; Best practice; Internet.